Thiophanate‐methyl and carbendazim resistance in Fusicoccum amygdali, the causal agent of constriction canker of peach and almond - Fontaine, Séverine; Caddoux, Laëtitia; Remuson, Florent; Barrès, Benoit (Plant pathology, 2022)
In light of growing environmental concerns, surveys of fungicide resistance are needed to ensure efficient control of fungi and avoid unnecessary treatments. Investigations of fungicide resistance in Fusicoccum amygdali are scarce despite the economic impacts of this pathogen in peach and almond orchards. Thiophanate‐methyl has been registered for more than 20 years to control F. amygdali but no resistance has been reported to date. This propesticide is metabolized by fungi into carbendazim, a β‐tubulin inhibitor. Sensitivity to carbendazim of nine populations of F. amygdali from French orchards was assessed using germination bioassays. Also, resistance levels of 63 strains isolated from four populations were evaluated using mycelial growth assays. The underlying mechanism of resistance was investigated by sequencing the β‐tubulin gene, the molecular target of thiophanate‐methyl, in a set of isolates with different levels of sensitivity to carbendazim. Cross‐resistance to thiophanate‐methyl and to another β‐tubulin inhibitor, diethofencarb, was also assessed in carbendazim‐sensitive and ‐resistant strains. Isolates highly resistant to carbendazim were found in one of the nine orchards studied. Sequencing showed that resistant phenotypes carry a mutation in the β‐tubulin gene leading to E198K substitution. Positive cross‐resistance to thiophanate‐methyl was confirmed and no negative cross‐resistance to diethofencarb was identified in the phenotyped isolates, which were all resistant to this active substance. To our knowledge, this is the first report of resistance to thiophanate‐methyl in F. amygdali. The high level of resistance of isolates sampled in one population is of concern, although the limited geographical scope of resistance suggests its recent emergence. We identified Fusicoccum amygdali isolates in France with a high level of resistance to thiophanate‐methyl and carbendazim. This resistance is linked to a target site mutation of the β‐tubulin gene.